PENERAPAN AJARAN WIDHI SRADHA DALAM MEMBENTUK KARAKTER SISWA PADA PASRAMAN WIDYASANA KABUPATEN SUKOHARJO - Wibowo, Gatot; Suherman; Lestari, Endang Sri (Widya Aksara : Jurnal Agama Hindu, 2024)
The instillation of moral, ethical and spiritual values in the young generation of Hindus through Pasraman education is a medium for the formation of personality and character development of students as a vehicle for the transformation of the teachings of Widhi Sradha in Hinduism which are beliefs and beliefs about the truth of Ida Sang Yang Widhi Wasa. In essence, it emphasizes the teachings of Tri Pramana which include Agama Pramana, Anumana Pramana and Pratyaksa Pramana with the principle that its implementation must be balanced in harmony between one and the other. If balance is achieved, a harmonious, peaceful and peaceful life will be realized. Pasraman Widhyasana in Sukoharjo Regency is a place to learn about learning that not only trains strengthening of the intellectual scope but balances emotional and spiritual intelligence as an institution for preparing Hindu human resources to become good citizens in the life of the nation and state based on Pancasila with the legal basis: Law No. 20 of 2003 Article 30 paragraphs 1, 3, and 4 (National Education System), Regulation of the Minister of Religion Number 56 of 2014 concerning the principles of Hindu religious education management, Government Regulation 55 of 2007 Article 1 paragraph (5) concerning Religious and Religion Education and Article 38 paragraphs (2) and (3) concerning the organization and management of pasraman.